Eksistensi Adat Kasiturusan dalam Pembagian Warisan Masyarakat Adat Toraja di Lembang Palesan Kabupaten Tana Toraja - Connie Else Pirade (LPPM Institut Pendidikan Nusantara Global, 2026)
In Toraja society, kasiturusan is not only an inheritance distribution mechanism but also a customary institution that sustains the tongkonan, strengthens kinship ties, and preserves cultural identity. In practice, kasiturusaninteracts with state law, creating dynamics of legal pluralism. This study aims to examine the existence of kasiturusan in the Toraja customary inheritance system and analyze its legal implications for heirs who either accept or reject it. This research applies a socio-legal approach, combining normative and empirical studies. Data were collected through literature review, legal document analysis, and theoretical frameworks involving legal pluralism theory, kinship theory, and sociology of law. The findings reveal that kasiturusan continues to strongly exist in Toraja society, though it has adapted to social, economic, and formal legal dynamics. Acceptance of kasiturusan reinforces the social position and customary legitimacy of heirs, while rejection results in the loss of symbolic rights, social exclusion, and potential disputes in the formal legal system. Kasiturusan serves a dual role as a cultural preservation institution and as a critical focal point in the dynamics of Indonesia’s legal pluralism. Therefore, proportional recognition by the state is necessary to avoid conflicts with the national legal system.